Implementación de una red de fibra óptica con normas estándares IEEE 802.3ae y ansi\tia\eia-568-b.3-1 con datos industriales plc para facilitar la seguridad y velocidad en la transmisión de datos en tiempo real entre hmi, servidores y plc, en el área de laminación del tren 1 de la empresa Novacero S.A. planta industrial Lasso, periodo 2014-2015 - Coyachamin Castro, Germanico Patricio (2016)
The present investigative work details the implementation of a optical fiber net with IEEE 802.3ae regulations and standards and ANSI/TIA/EIA-568-B.3-1 with PLC industrial data, with the aim of facilitating safety and to offer better agility and rapidness in data transmission that are sent through it. This implementation was carried out in the gate number one in the lamination area at the Novacero Enterprise Industrial Plant S.A. since the former net was damaged, besides this was implemented totally with UTP structured cable in this part of the enterpriser, which indicated slowness and instability at the moment of transmitting data. For the implementation of the net, regulations and IEE 802.3 standards were applied, which has multiple accessing with a speed of 10 Gigabit connected to physical means with structure cabling of optical fiber. Besides, it has characteristics relate to the physical surface which resemble speed, support, type of signal and the length of the segment. It also counts with ANSI/TIA/EIA, using these means, it is possible to identify the minimum requirements for the optical fiber components, and at the same time it shows the requirements that the optical fiber for structured cabling has to fulfill in order to support the serial transmission of 10 Gbps, being the required velocity for data transmission. By carrying out the implementation of the optical fiber and then making the corresponding tests for transmission velocity and data safety, it was evident that there is a great variation in the registered time previously with the former cabling, these tests allowed to give validity to the hypothesis that was established in this work, which guarantees its validity.